HUBUNGAN KEBIASAAN MEROKOK DENGAN GANGGUAN POLA TIDUR PADA REMAJA - Budi Kristanto; Ahmad Sarif (KOSALA : Jurnal Ilmu Kesehatan, 2017)
For some people, smoking has become a necessity of life that can not be abandoned ineveryday life - the day. Results Health Research in 2013, the smoking behavior ofpopulation aged 15 years and over or adolescence is still a decline from 2007 to 2013, islikely to increase from 34.2% in 2007 to 36.2% in 2013.This research uses correlation study with cross sectional approach to determine therelationship of smoking as an independent variable with disruption of sleep patterns inadolescents as the dependent variable. The population in this study were all adultsmokers in the village of Wangkah Gedangan Grogol, Sukoharjo, ie a total of 30adolescent smokers. Researchers using a questionnaire with questions about the amountto 3 point for an overview of smoking and 10 of the questions for the description of sleepdisorders. The data obtained then tabulated tabulation and analyzed using SPSS 16 forWindows.Research result: 1) From the results of this study can be obtained that the majority ofrespondents, a number of 15 (50%) to the category of light smokers, while 9 respondents(30%) to the category of moderate smokers, and 6 respondents (20%) categories ofheavy smokers. 2) The majority of respondents with moderate sleep disorder category,the number of 24 respondents (80%), while 4 respondents (13.3%) with mild sleepdisorder category, and 2 respondents (6.7%) with severe sleep disorder category. Of allrespondents were 30 teenage 100% impaired sleep patterns. 3) Pearson Chi-Square5.513889, where <of Î±: 0:05. It can be concluded that there is no relationship betweensmoking category by category disruption of sleep patterns. Linear or non smokingcategory to the category of sleep disorders.Keywords: Smoking, disruption of sleep patterns, teen age